New recourse to flood victims in Malaysia: a proposal on permanent Waqf flood evacuation centre - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani; Che Embi, Nor Azizan; Megat Laksana, Nan Noorhidayu (International Research Centre of Islamic Economics and Finance (IRCIEF), International Islamic University College of Selangor (KUIS), Malaysia and Sultan Sharif Ali Islamic University (UNISSA), 2017)
A flood phenomena in Malaysia is considered as a yearly event that most of the time hit the east coast area of Malaysia (Kelantan, Terengganu, and Pahang). It is also understood that when the flood happen, government would spent certain amount of money to cover damages and losses because of the flood. As the flood may affect the society on the whole, we should think how to assist the flood victims and at the same time reduce the government expenses on the flood. This research therefore is conducted to investigate the effect of flood to society in terms of financial, health, source of income, and property. This research also observes the experience of the flood victims staying at the flood evacuation centre, and finally proposes a permanent flood evacuation centre base on Waqf principle. To achieve the stated objectives, case study on two flood prone areas which are Tumpat and Pasir Puteh located in Kelantan is conducted. Overall, it is found that flood have affected the victims (villages) in terms of financial, health, sources of income as well as properties where some of them have to borrow money from relatives or friends to bear all the losses caused by flood. Besides that, asking about their experiences staying at the flood evacuation centre, majority of the victims have satisfied with the food and other necessities prepared for them. Unfortunately, among bad experiences that they had during their stay were basically in terms of cleanliness of the centres, Shariah issues that emerged because of the arrangement of the spaces, and also limited activities conducted to children or parents. This research thus, suggesting a permanent flood evacuation centre based on Waqf principle to enhance the existing management of flood evacuation centres. The proposed centre would cover both physical and spiritual aspects to the flood victims where appropriate activities or module will be structured for the children as well as the parents to enhance their skills and increase their living standard in future. Interestingly, all the respondents accept this suggestion positively and were happy on our proposal towards establishing permanent waqf flood evacuation centre. This research thus is significant in giving suggestion to the authority to build permanent flood evacuation centres using the waqf principle that provide avenue to the villages (low income group) to enhance their income and increase their standard of thinking and living.